"I Hear a Tenor Saxophone, Who's Playing it, Chombi?" P. Ramlee's Films as Music Classrooms - Raja Iskandar Raja Halid (2011)
P. Ramlee (1929-1973) was a Malaysian film actor, director, singer and songwriter. Throughout his career, P Ramlee was involved in more than sixty films and wrote more than 200 songs, Besides highlighting social foibles, taboos and issues, P.Ramlee's films were also canvases where he experimented with his musical ideas. His songs were as well known as his films - they were inseparable. Songs such as " Getaran Jiwa", " Di Mana Kan Ku Cari Ganti" and "Jeritan Batinku" became hugely popular and made him one of the best singers/ songwriters in the history of modern Malay music. His films were also : musicclassroom" where audiences were taught basic knowledge about Western music such as theory, intrumentation and caree prospects. This paper looks into the variety of musical influences that shaped his songs and how his films were used in educating his audiences.